Factors That Influence the Choice to Undergo Surgery for Shoulder and Elbow Conditions - Modi, Chetan S. (Springer US, 2013)
BACKGROUND: Knowledge of the factors that influence the willingness of patients considering elective orthopaedic surgery is essential for patient-centered care. To date, however, these factors remain undefined in the orthopaedic population with shoulder and elbow disorders. QUESTIONS/PURPOSES: In a cohort of patients seeking surgical consultation for shoulder or elbow conditions, we sought to identify factors that influenced the willingness and decision to undergo surgery. METHODS: In this prospective study, 384 patients completed a questionnaire collecting socioeconomic and health status data before consultation from June 2009 to December 2010. An additional 120 patients who were offered surgery after consultation completed a second questionnaire on their perceptions and concerns regarding surgery. Logistic regression analyses were used to identify factors influencing the willingness and decision to undergo surgery. RESULTS: Lower income (odds ratio [OR], 0.02; CI, 0.02–0.08; p < 0.001) and living alone (OR, 0.25; CI, 0.08–0.77; p = 0.015) were negative predictors of willingness to consider surgery. Physical functioning did not influence willingness (p = 0.994). A greater perceived level of the likelihood of surgical success by the patient (OR, 41.84; CI, 5.24–333.82; p < 0.001) and greater fluency in the English language (OR, 28.39; CI, 3.49–230.88; p = 0.002) were positive predictors of willingness. Willingness to consider surgery as a possible treatment option before the consultation was a predictor of patients’ ultimate decisions to undergo surgery (OR, 4.56; CI, 1.05–19.76; p = 0.042). Patients expressing concern about surgery being an inconvenience to daily life, however, were less likely to decide to proceed with surgery (OR, 0.12; CI, 0.02–0.68; p = 0.017). CONCLUSIONS: Many of the identified factors may act as barriers to potentially beneficial surgical interventions. Although most are not modifiable, an awareness of the influence of individual demographics and possible perceptions of patients’ choices may show that more in-depth questioning and provisions for cultural differences may be required during the consultation to enable patients to make fully informed decisions. Future studies using qualitative methods would provide a greater in-depth understanding of patients’ perceptions regarding surgery and their decision to proceed. Larger or more homogeneous cohorts also would enable additional identification of these factors for different shoulder and elbow conditions. LEVEL OF EVIDENCE: Level II, prognostic study. See the Instructions for Authors for a complete description of levels of evidence.